Analyzing the Impact of FinTech Adoption on Financial Inclusion and Economic Development: A Data-Driven Approach - Abouraia, Mahmoud Kamal; Al Morsey, Dr. Rania Mohamed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This research study provides a comprehensive analysis of the impact of FinTech adoption on financial inclusion and economic development in the Indian context, employing a data-driven approach. The analysis, based on correlational data presented in several tables, highlights the interdependencies between FinTech adoption, financial inclusion, and economic development. The findings emphasize the pivotal role of technology in fostering inclusive growth and resilience, as demonstrated by the fluctuations in GDP growth rates and the upward trend in banking penetration, particularly in rural areas. Furthermore, the disparities in FinTech adoption across different Indian states underscore the importance of targeted strategies to bridge regional technological gaps and ensure equitable access to digital financial services. The research also showcases the significant progress of the Indian FinTech sector, with substantial investments and a burgeoning number of startups, aligning with global trends in the transformative role of technology in reshaping the global financial landscape. The findings collectively underline the significance of fostering collaborative partnerships, strengthening regulatory frameworks, and promoting digital literacy to ensure sustainable and inclusive growth in the Indian FinTech sector, in alignment with global best practices and technological advancements.